PHENOMENOLOGICAL STUDY: TIKTOK LIVE SHOPPING HOSTS IN PERSUASIVE COMMUNICATION - Nasywa Astrid Indriani; Azwar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to understand the meaning, motives, and experiences of TikTok live shopping hosts in applying persuasive communication through Alfred Schutz's phenomenological approach. The results show that hosts have meaning in facilitating trust, building credibility, and transforming symbols of persuasive communication. Host motives are divided into “because of” motives rooted in background, and “in order to” motives oriented toward future goals. The hosts' experiences include understanding the flow of activities, using verbal and non-verbal symbols, and effective time management in live shopping. The integration of social and technological aspects proves that live shopping builds a comprehensive digital shopping experience and that the hosts' persuasive communication is the main foundation that transforms the audience's doubts into trust. Thus, this study provides theoretical contributions to the study of digital communication and practical contributions to the development of e-commerce through live shopping.